Examining Customer Loyalty in Using Gold Pawn Products at PT. Bank Sulselbar Syariah Palopo - Annisanisa; Abid; Sahrir (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research aims to examine customer loyalty in using gold pawning products at PT Bank Sulselbar Syariah Palopo. This research uses qualitative research methods with close descriptive analysis. The research obtained data through questionnaires, interviews and direct observation with customers who used the Islamic gold pawn (rahn) product of Bank Sulselbar Syariah Palopo as the research location and conducted interviews with customers, and the Head of Bank Sulselbar Syariah Palopo who was considered to continue to provide the information needed by researchers. The research results reveal that customer loyalty in using gold pawn products (rahn) at Bank Sulselbar Syariah Palopo is very high because they make regular repeat purchases, buy between product and service lines, refer to others, show immunity to the pull of competitors, performance, price , and ease of obtaining. There are factors that influence customers in using Bank Sulselbar Syariah Palopo's gold pawn (rahn) products, namely service, promotional, economic and religious factors.